Electrochemistry of Iodide in LiCl-KCl Molten Salts and Chemla Effect: An Overview. (10th April 2018) - Shrestha, Nikunja; Day, Brandon; Utgikar, Vivek; Raja, Krishnan S.; Fredrickson, Guy; Frank, Steven
Abstract : Several radioactive iodine isotopes are formed as fission products in the nuclear fuel, and retained within the fuel matrix by the fuel cladding as containment. During reprocessing of the used fuels by the pyroprocessing route, a significant fraction of iodine is reported to be retained in the molten salt as iodide (I - ). The oxidation of I - is strongly influenced by the Cl - . When Cl - concentration is in excess of I -, the iodide oxidizes to [ICl2 ] - in two single electron steps via an [I2 Cl] - intermediate. The presence of chloride leads to oxidation of I3 - to occur at less positive potentials. Chemla effect of type 1 has been observed in the LiCl-KCl molten salt systems wherein the mobility of the K + is larger than that of Li + when the fraction of KCl is higher than 0.325 at 723 K. The Chemla effect could lead to accumulation of KCl near the cathode and adversely influence the electrolytic parameters.